Visibilización de dificultades educativas: Los retos del gobierno colombiano y de las comunidades educativas para afrontarlas - Montero Mahecha, Luz Stella (Universidad de Costa Rica, 2021)
This essay is carried out in order to publicize the difficulties that Colombian public education has faced and the inequity that has become visible with the arrival of the Covid-19 pandemic. For this, various difficulties are analyzed, such as the lack of a solid Institutional Educational Project, the absence of connectivity and the insufficiency of tools and technological knowledge of all the actors of the educational community, which have a background lack of knowledge in the management of digital tools and / or the scarcity of economic resources, as well as the absence of self-learning habits. Hence, it is necessary that all the actors involved in the educational process, with commitment, play the role that corresponds to them, in such a way that the curriculum is fully complied with, regardless of the circumstances that surround it. The conclusion establishes the responsibility that the State must assume in the allocation of resources for education and support to the communities, the commitment of the school to lead the continuous harmonization with an IEP adapted to the context and susceptible to unschooling, the a task that students must fulfill to autonomously approach the educational process and the importance of preparing families to face the needs of today's education.